Improvement of Program Machining Efficiency by Eliminating One Cutter Ball Nose to Lower Dies Manufacturing Costs - Lilik Suwito; Eko Muh Widodo; Tuessi Ari Purnomo (Urecol Journal. Part E: Engineering, 2021)
The tooling department is a department that is engaged in manufacturing dies, namely the manufacture of printing equipment to make a component / pressed part which is made according to the desired design and processed on a press machine, dies are ordered from the customer, namely the sole agent of the brand (ATPM). Manufacturing dies including project work, one of the dies manufacturing projects is the 640A dies drawing part number 53711/12 project with the current machining program time being efficient at 47.29%, but to improve service to the sole agent of the brand holder and to reduce the cost of manufacturing dies, it is necessary to increase efficiency by eliminating one ball nose cutter. This research was conducted with the aim of obtaining a more efficient machining program by conducting technical analysis on the machining program dies drawing 53711/12. Technical analysis was carried out on the 12 mm ball nose cutter and 10 mm ball nose cutter by calculating the path length, cutter load and cutter life so as to obtain elimination results on the 10 mm ball nose cutter because the cutter was less effective. The result of the elimination of one cutter is that the percentage of machining program efficiency increases to 48.72% and affects the efficiency of purchasing cutters by 4.15% and efficiency in manufacturing costs for dies drawing part number 53711/12 increased from 5.44% to 5.71%, an increase of 0.27% or Rp 1,833. 893.06